1992
DOI: 10.1002/jmor.1052140311
|View full text |Cite
|
Sign up to set email alerts
|

Functional implications of neural canal anatomy in recent and fossil marine carnivores

Abstract: A statistical and functional relationship between neural canal anatomy and locomotor mode is demonstrated in living marine mammals of the Order Carnivora. This relationship is interpreted to be the result of differential innervation and territory of musculature involved in generating the six locomotor patterns analyzed. This osteological reflection of a behavioral trait allows prediction of locomotor pattern in extinct genera of closely related taxa. The robust data allow such predictions even when a considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…All of these morpho-functional features are consistent with pelvic oscillation. Consequently, this study supports Giffin's (1992) interpretation that A. kernensis used a combination of fore-and hindlimb movements during aquatic locomotion. Considering the limbs in A. kernensis suggest an otariid-like swimming movement (Mitchell, 1966;Bebej, 2009) and the vertebral column points towards a mixed pattern (Giffin, 1992; this study), we propose that the locomotor style of A. kernensis was most likely the opposite to that found in Odobenus, with the large foreflippers as the primary propulsive force and the smaller hindflippers and mechanically active lumber region being used secondarily to drive the animal through the water column.…”
Section: Allodesmussupporting
confidence: 87%
See 2 more Smart Citations
“…All of these morpho-functional features are consistent with pelvic oscillation. Consequently, this study supports Giffin's (1992) interpretation that A. kernensis used a combination of fore-and hindlimb movements during aquatic locomotion. Considering the limbs in A. kernensis suggest an otariid-like swimming movement (Mitchell, 1966;Bebej, 2009) and the vertebral column points towards a mixed pattern (Giffin, 1992; this study), we propose that the locomotor style of A. kernensis was most likely the opposite to that found in Odobenus, with the large foreflippers as the primary propulsive force and the smaller hindflippers and mechanically active lumber region being used secondarily to drive the animal through the water column.…”
Section: Allodesmussupporting
confidence: 87%
“…It was originally thought that A. kernensis primarily used its forelimbs in aquatic locomotion (Mitchell, 1966; Barnes, 1972). However, analysis of the functional implications of neural canal anatomy by Giffin (1992) showed that both its fore‐ and hindflippers were quite heavily innervated, a pattern most consistent with carnivores that use both the fore‐ and hindlimbs during swimming. Berta & Adam (2001) claimed that A. kernensis retains several features consistent with forelimb propulsion but also displays adaptations for hindlimb swimming, although no details are given.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…She was able to use neurological evidence to infer forelimb use in theropods via examination of data on their brachial enlargements: theropods with proportionally small forelimbs like Tyrannosaurus and Carnotaurus have comparatively smaller brachial enlargements than do Deinonychus and Saurornitholestes (Giffin ). This method has also been successfully applied to modern and fossil marine carnivorans (Giffin ). Similarly, small brachial enlargement size in Haast's eagle ( Harpagornis moorei ) was used to suggest it lacked the neural development required for fine motor control, implying it could not have hunted in densely packed forests (Scofield & Ashwell ).…”
Section: Institutional Abbreviationsmentioning
confidence: 99%
“…Although most paleoneurological studies have been concerned almost exclusively with what the braincase can tell us about the brain (e.g. Edinger, 1941;Radinsky, 1968;Jerison, 1973;Hopson, 1979), the neural canal can also yield information about the spinal cord and its control of the postcranial vertebrate body (Giffin, 1990(Giffin, , 1992. This project is guided by the phylogenetic and extrapolatory techniques for inference of unpreserved attributes of extinct taxa defined by Bryant & Russell (1992).…”
Section: Introductionmentioning
confidence: 99%